New horizons in criminal legal data: creating a comprehensive archive - Katherine LeMasters; Erin McCauley; Lauren Brinkley-Rubinstein (BMC, 2024)
Abstract While criminal legal involvement is a structural determinant of health, both administrative and national longitudinal cohort data are collected and made available in a way that prevents a full understanding of this relationship. Administrative data are both collected and overseen by the same entity and are incomplete, delayed, and/or uninterpretable. Cohort data often only ask these questions to the most vulnerable, and do not include all types of criminal legal involvement, when this involvement occurs in someone's life, or family and community involvement. To achieve a more optimized data landscape and to facilitate population-level research on criminal legal involvement and health, (1) individual administrative level data must be made available and able to be linked across carceral systems, (2) a national data archive must be made to maintain and make criminal legal data available to researchers, and (3) a nationally representative, longitudinal study focused on those with criminal legal involvement is necessary. By beginning to critically think about how future data could be collated and collected, we can begin to provide more robust evidence around how the criminal legal system impacts the health of our society and, in turn, create policy reform.